Gender dysphoria and a de-transition to the biological gender : a case report from a primary care perspective - Fathima Begum SM; Hizlinda Tohid; Mohd Radzniwan Rashid; Sharifah Najwa SM; Khadijah Hasanah AA; Hatta Sidi (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Gender dysphoria describes the feeling of distress and discomfort experienced when the assigned gender does not match the person’s gender identity. In its severe form, it leads to anxiety, depression and even suicidal ideation or attempts. Unfortunately, this does not end as some transgenders faced significant pressure by cultural, religious, employment, financial and social during the transformation period, hence would de-transition back to their natal gender identity. Gender detransition is a process through which a person discontinues some or all aspects of gender affirmation. During the de-transition, ambivalence, confusion, doubts about their ability to carry out the gender role and responsibilities are common. Gender dysphoria and gender de-transition requires professional help, but the stigma and discrimination hinders them from seeking help from health care providers (HCP). Although these gender-related identity problems are preferentially diagnosed by a specialised psychologist or psychiatrist, primary care physicians often play an important role in this aspect. This case illustrates the health and help-seeking behaviour of a transwoman who had experienced gender dysphoria in the early adolescence year. Long after that, he faced a difficult life, making him de-transition to his original gender. He eventually presented with trivial symptoms in primary care hoping to solve the crisis.